Study of electrode performance for nanosized La0.4Sr0.6Co0.8Fe0.2O3-δIT-SOFC cathode - Mogni, Liliana Verónica (2015)
La0.4Sr0.6Co0.8Fe0.2O3-δ (LSCF4682) perovskites were successfully synthesized by an assisted ammonium nitrate combustion method. The sample shows a sponge-like structure with meso and macro-pores channels distributed between interconnected nanosized particles (~45 nm) with a high specific surface area. Cathode performance of LSCF4682 was investigated in the intermediate temperature range of 400°C-700°C by using symmetrical cell configuration on La0.8Sr0.2Ga0.8Mg0.2O3-δ (LSGM) electrolyte. The cathode polarization resistances Rc,p are 0.067 and 0.035 Ω·cm2 at 600°C and 700 °C, respectively. The long-term behavior of Rc,p was studied by applying an accelerate aging at 800 °C and testing the polarization resistance at 700°C as a function of time. After 500 h of aging, a degradation rate of (1/RC,P)(dRC,P/dt)= 0.002 h-1 raises the Rc,p to 0.1 Ω·cm2 at 700°C. A maximum power density of 1.23 Wcm-2 was achieved at 650 °C testing the LSCF cathode deposited on a porous SLT-LSGM supported multilayer cell. The results demonstrate that this material is a competitive SOFC cathodes for the intermediate temperature operation.